Composite implants coated with biodegradable polymers prevent stimulating tumor progression - Litvyakov, Nicolay V.; Tverdokhlebov, Sergey I.; Perelmuter, Vladimir M.; Kulbakin, Denis E.; Bolbasov, Evgeny N.; Tsyganov, Matvey M.; Zheravin, Aleksandr A.; Svetlichnyi, Valerii A.; Cherdyntseva, Nadezhda V. (AIP Conference Proceedings)
In this experiment we studied oncologic safety of model implants created using the solution blow spinning method with the use of the PURASORB PL-38 polylactic acid polymer and organic mineral filler which was obtained via laser ablation of a solid target made of dibasic calcium phosphate dihydrate. For this purpose the implant was introduced into the area of Wistar rats' iliums, and on day 17 after the surgery the Walker sarcoma was transplanted into the area of the implant. We evaluated the implant's influence on the primary tumor growth, hematogenous and lymphogenous metastasis of the Walker sarcoma. In comparison with sham operated animals the implant group demonstrated significant inhibition of hematogenous metastasis on day 34 after the surgery. The metastasis inhibition index (MII) equaled 94% and the metastases growth inhibition index (MGII) equaled 83%. The metastasis frequency of the Walker sarcoma in para aortic lymph nodes in the implant group was not statistically different from the control frequency; there was also no influence of the implant on the primary tumor growth noted. In case of the Walker sarcoma transplantation into the calf and the palmar pad of the ipsilateral limb to the one with the implant in the ilium, we could not note any attraction of tumor cells to the implant area, i.e. stimulation of the Walker sarcoma relapse by the implant. Thus, the research concluded that the studied implant meets the requirements of oncologic safety.